Conservative management of a transdiaphragmatic fistula. Issue 5 (1st May 2000) - Gee, I; Wood, G M
Abstract : Case reports of transdiaphragmatic fistulas connecting subphrenic collections and empyemas are uncommon. We report the rare complication of a fistulous connection between a subphrenic collection and the bronchial tree.